A system of indicators for the complex evaluation of the tax system - Bivainis, Juozas; Skačkauskienė, Ilona (Business: Theory and Practice, 2009)
The main problem examined in the current article is the evaluation of tax system. It is suggested that tax systems should be evaluated through the hierarchical evaluation system consisting of primary, partially-integrated and complex-integrated indicators. Primary non-recurrent indicators are classified into three groups and aimed at evaluating a tax system through the prism of a certain aspect. The system is built taking into consideration the requirements of consistency, comparability and simplicity, and aimed at objective and accurate evaluation of tax systems. The synthesis of partially integrated indicators creates preconditions for complex evaluation of tax systems enabling identification of the quality of tax systems and comparison of tax systems of various countries. Complex tax system evaluation provides with a possibility to conduct a systematic analysis and to generate a quantitative estimate. The recommended complex tax system evaluation creates preconditions to analyse tax systems as a uniform totality, to identify their standing in various aspects correlated in quantitative terms, and to carry out dynamic and comparative analyses. Interstate comparative analysis of tax systems creates preconditions to reveal relevant quality of tax systems in various countries, to crystallise out the best practices that could be used for improvement of the quality of the tax system in the country at issue. Also, the evaluation system could be adapted to various needs of the evaluator: classification of indicators into groups enables elimination of some indicators or introduction of new ones without destroying the established system of significance of the indicators, simply by adjusting significance levels within the group. Article in Lithuanian. Kompleksinio mokesčių sistemos vertinimo rodiklių sistema Santrauka. Straipsnyje nagrinėjama mokesčių sistemos vertinimo problema. Atskleidus esamų vertinimo metodų spragas, mokesčių sistemai vertinti pasiūlyta hierarchinė vertinimo sistema, kurią sudaro pirminiai, daliniai integruoti ir kompleksiškai integruoti rodikliai. Pirminių nesikartojančių rodiklių, suskirstytų į tris grupes, skirtas mokesčių sistemai tam tikru aspektu vertinti, sistema suformuota atsižvelgiant į visapusiškumo, lyginimo ir paprastumo reikalavimus bei siekiant objektyviai ir tiksliai įvertinti mokesčių sistemą. Dalinių integruotų rodiklių sintezė sudaro prielaidas vertinti kompleksiškai. Tai leidžia nustatyti mokesčių sistemos kokybę ir lyginti įvairių šalių mokesčių sistemas. Kompleksinis mokesčių sistemos vertinimas suteikia galimybę atlikti mokesčių sistemos kaip visumos sisteminę analizę ir gauti kiekybinį įvertį. Reikšminiai žodžiai: mokesčių sistema, sisteminė analizė, daugiakriterinis vertinimas. First Published Online: 10 Dec 2009